Divergence between strength indicators in packaging and cigarette engineering: a case study of Marlboro varieties in Australia and the USA. Issue 5 (7th June 2010) - King, Bill; Borland, Ron; Abdul-Salaam, Shadeed; Polzin, Gregory; Ashley, David; Watson, Clifford; O'Connor, Richard J
Abstract : Objectives: To investigate how the tobacco industry is adapting to regulatory action in accordance with provisions of the Framework Convention on Tobacco Control that targets misleading packaging and labelling. To relate the packaging and labelling of new cigarette varieties to their construction and performance. Methods: The principal design features and tar, nicotine and carbon monoxide yields of the Marlboro 'brand family' in Australia were measured and compared with those of the US equivalents. Results: Marlboro Red and Blue/Medium, could not be differentiated in preliminary tests in Australia, but were different in the USA. However, yield testing showed Marlboro Blue/Medium did not have lower tar and nicotine yields in either country, indeed being higher in Australia. Conclusions: Colour can be used to market cigarettes as 'milder', independently of ISO yields and 'Light'/'Mild' descriptors. Banning of 'Light' and 'Mild' brand descriptors may be inadequate to end belief in less harmful cigarettes so long as the tobacco industry remains free to engineer 'mildness' and to use colours, other descriptors and design features to characterise varieties it wants to market as 'milder'.